Review of The Water Carrying Capacity and Water Flow at RDTR of The Spatial Planning of Tegalluar Residential Integrated Area in Bandung Regency - Budi Heri Pirngadi; Deden Syarifudin; M. Zaenal Ramdhani As Siddiq (Journal of Community Based Environmental Engineering and Management, 2023)
The development of Tegalluar area as a strategically planned integrated residential center, potentially serving as the new provincial government center for West Java, stands as a top priority for the Bandung Regency Government. To support this vision, the Regional Detailed Spatial Plan (RDTR) for Tegalluar Integrated Settlement Area and the Planning Area (BWP) of Bojongsoang have been formulated. Concurrently, the region has grappled with persistent water resource management challenges, marked by annual flooding during the rainy season and water shortages in the dry season. This research aims to comprehensively analyze the water flow cycle within the area and explore potential scenarios for water management in alignment with the RDTR. The research findings reveal that, in the development scenario, the water flow pattern remains largely unchanged, with limited efforts to harness rainfall or manage wastewater. Precipitation and surface water predominantly contribute to the water inflow in the research area. Furthermore, the provision of clean water heavily relies on external sources. Based on this water flow analysis, there exists an opportunity to implement water-sensitive urban design principles in the research area. This involves capturing rainwater through effective harvesting techniques and adopting wastewater reuse strategies, focusing on non-potable applications. Such measures can enhance water sustainability and mitigate the region's water-related challenges.